EXPLORING ENGLISH MONOPHTHONGS PERCEPTION AND PRODUCTION IN MALAYSIA - Raja Rosemawati Raja Abdullah, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This abstract presents a comprehensive overview of the challenges and considerations surrounding the effective communication of English as a second language (ESL) among Malaysian learners. While verbal and written communication forms are essential in daily interactions, language proficiency and accurate pronunciation are integral to successful message transmission. The Malaysian context, where English is a secondary language frequently employed for formal communication and international discourse, underscores the significance of proficient language use. Despite the prevalence of English instruction, students often excel academically but struggle to apply the language practically, especially in pronunciation. The prevailing emphasis on examination performance over practical language skills contributes to this disparity. Research indicates that ESL learners face difficulties accurately articulating sounds, leading to misunderstandings and inhibiting practical discourse. These challenges are further exacerbated by socio-cultural perceptions that tie accurate pronunciation to professionalism and social status. Efforts to address this issue include the Kurikulum Standard Sekolah Rendah (KSSR), which aims to cultivate well-rounded language skills among students. However, the practical application of English, particularly pronunciation, remains an area of concern. By exploring the complex interplay between language acquisition, educational strategies, and cultural perceptions, this abstract highlights the need for a holistic approach to ESL communication. By recognising the multifaceted nature of language proficiency and prioritising practical language skills alongside theoretical knowledge, Malaysia can better equip learners to engage confidently and effectively in English discourse. Ultimately, the abstract emphasises the importance of nurturing a generation of English language users who can navigate the demands of global communication and contribute to the challenges of the modern world.